Microspherical Titanium-Phosphorus Double Oxide: Hierarchical Structure Development for Sensing Applications - Elena Korina; Anton Abramyan; Oleg Bol’shakov; Vyacheslav V. Avdin; Sladjana Savić; Dragan Manojlović; Vesna Stanković; Dalibor M. Stanković (Sensors, 2023)
Stable, water-soluble titanium complexed with mandelic acid was used as a precursor for titanium phosphorus double oxide obtained in hydrothermal conditions in the presence of phosphoric acid. Surprisingly, hydrolysis of organic complexes provided a microstructured sphere with narrow size distribution, low aggregation and a small fraction of morphological irregularities. Obtained microspheres had a complex structure comprised of flakes, whose size could be manipulated with temperature conditions. Samples were found to be electrochemically active against sulcotrione, a well-recognized herbicide. Electrochemical sensors based on the synthesized microspheres were successfully adapted for natural water reservoir analysis and exhibited low levels of detection of 0.61 µM, limit of quantification of 1.86 µM, wide dynamic linear range from 2 to 200 µM, good selectivity, excellent reproducibility and in-time stability.